2013
DOI: 10.1371/journal.pone.0070352
|View full text |Cite
|
Sign up to set email alerts
|

Role of CTLA4 in the Proliferation and Survival of Chronic Lymphocytic Leukemia

Abstract: Earlier, we reported that CTLA4 expression is inversely correlated with CD38 expression in chronic lymphocytic leukemia (CLL) cells. However, the specific role of CTLA4 in CLL pathogenesis remains unknown. Therefore, to elucidate the possible role of CTLA4 in CLL pathogenesis, CTLA4 was down-regulated in primary CLL cells. We then evaluated proliferation/survival in these cells using MTT, 3H-thymidine uptake and Annexin-V apoptosis assays. We also measured expression levels of downstream molecules involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…In contrast, Mittal and colleagues described that CTLA-4 expression on CLL cells is generally associated with good clinical outcome and that the presence of a polymorphism of CTLA-4 is correlated to increased risk and advanced Rai stages in CLL [49]. They showed that in vitro CTLA-4 down-modulation increases the proliferation rate of leukemic cells and upregulates surface expression of CD38, a well-known marker of high-risk CLL, together with the expression of STAT1, NFATC2 and c-Myc, which represent downstream molecules of the B-cell proliferation/survival signaling pathway [50].…”
Section: Cytotoxic T Lymphocyte Antigen-4 (Ctla-4)/b7mentioning
confidence: 99%
“…In contrast, Mittal and colleagues described that CTLA-4 expression on CLL cells is generally associated with good clinical outcome and that the presence of a polymorphism of CTLA-4 is correlated to increased risk and advanced Rai stages in CLL [49]. They showed that in vitro CTLA-4 down-modulation increases the proliferation rate of leukemic cells and upregulates surface expression of CD38, a well-known marker of high-risk CLL, together with the expression of STAT1, NFATC2 and c-Myc, which represent downstream molecules of the B-cell proliferation/survival signaling pathway [50].…”
Section: Cytotoxic T Lymphocyte Antigen-4 (Ctla-4)/b7mentioning
confidence: 99%
“…idenced low proliferative index, and higher Ki-67 expression was identified in samples from patients with advanced clinical stage or after cytokine stimulation [16][17][18][19][20][21][22] . Similar results were obtained with an in vitro proliferation study of MCL cells 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Literature mining analysis significantly associated it with apoptosis and cell-proliferation. CTLA4 has been reported to regulate key genes involved in carcinogenesis like STAT1, NFATC2, c-Fos, c-Myc, and/or Bcl-2 [39] . Literature mining analysis and mining of TTD have identified CTLA4 as a therapeutic marker for various cancers.…”
Section: Resultsmentioning
confidence: 99%